The missing reason for the step "ST = SU + UT" is the Segment Addition Postulate. This postulate states that the length of a segment is equal to the sum of the lengths of its parts.
So, the completed proof with the missing reason would include:
- ST = SU + UT (Segment Addition Postulate)
Here's the complete argument for the theorem:
- Given: SU is the midsegment of trapezoid WXYZ.
- SU || WX and UT || ZY (definition of midsegment in trapezoid).
- SU is the midsegment of triangle WXZ.
- UT is the midsegment of triangle XYZ (definition of midsegment in triangle).
- SU = 1/2 WX and UT = 1/2 ZY (Midsegment Theorem).
- ST = SU + UT (Segment Addition Postulate).
- ST = 1/2 WX + 1/2 ZY (substitution).
- ST = 1/2 (WX + ZY) (Distributive Property).
This shows that the length of the midsegment ST is half the sum of the lengths of the bases WX and ZY.